A 28 GHz HBT vector modulator and its application to an LMCS feedforward power amplifier - McPherson,DS; Stubbs,MG; Wight,JS; Lucyszyn,S (IEEE, 2007)
A vector modulator employing four amplitude modulated orthogonal channels is presented. Operating at 28 GHz, this device consists of a four-way 6 dB power divider, four GaAs HBT MMIC variable gain amplifiers, and a 4-to-1 power combiner All of the passive functions were realised on alumina ceramic while the amplifier chips were fabricated at Nortel Technologies using a 3.5 μm × 6 μm GaInP-GaAs HBT process. By testing a vector modulator prototype, we were able to evaluate the architecture and be the first to assess its suitability as a gain/phase control element for a Ka-band MCS adaptive feedforward lineariser.